3D‐MIMO beamforming realised by AQPSO algorithm for cylindrical conformal phased array. Issue 15 (1st November 2019) - Jiang, Xing; Xie, Ming‐cong; Wei, Jia; Wang, Kun‐peng; Peng, Lin
Abstract : Three‐dimensional (3D)‐MIMO beamforming realised by adaptive quantum particle swarm optimisation (AQPSO) algorithm for the 36‐element cylindrical conformal phased array is proposed in this study. The cylindrical conformal phased array consists of 36 circularly polarised microstrip antenna elements with ultra‐wideband and high gain characteristics. The conformal array is divided into 12 subarrays using reconfigurable technology, and each subarray produces six beams to cover the corresponding spatial area. The 3D‐MIMO beam is formed by AQPSO, and the active element pattern data of array elements is introduced to AQPSO to improve the accuracy of the algorithm. The simulated and measured results show that the cylindrical conformal phased array can achieve 3D‐MIMO beam coverage from 0° to 360° in the azimuth plane and from 67.5° to 112.5° in the elevation plane. It can be applied for satellite communication and fifth‐generation base station communication.